Normal Curves in 4-Dimensional Galilean Space G4 - Mosa, Safaa; El-Fakharany, Mohamed; Elzawy, Mervat (Frontiers in Physics, 2021)
In this article, first, we give the definition of normal curves in 4-dimensional Galilean space G4. Second, we state the necessary condition for a curve of curvatures τ(s) and σ(s) to be a normal curve in 4-dimensional Galilean space G4. Finally, we give some characterizations of normal curves with constant curvatures in G4.